Growth and Production of Grass Axonopus Compressus, Stenotaphrum Secundatum, and Paspalum Conjugatum at Various Biourine Level - N. P. L., Mertaningsih; Suryani, N. N.; Duarsa, M. A. P. (Jurnal Peternakan Tropika, 2019)
The research aimed to know the growth and production of Axonopus compressus , Stenotaphrum secundatum , and Paspalum conjugatum grasses at various of levels biourine. The research was conducted for 12 weeks in Sading Village, Mengwi District, Badung Regency. Completely randomized design (CRD) with split plot pattern was applied in this experiment. The first factor (main plot) was the type of grass, namely Axonopus compressus (R1), Stenotaphrum secundatum (R2) and Paspalum conjugatum (R3). The second factor (sub plot) was the level of biourine, namely: without biourine (B0), biourine 2000 l/ha (4 ml/4 kg) (B1), biourine 4000 l/ha (8 ml/4 kg) (B2), biourine 6000 l/ha (12 ml/4 kg) (B3). From these factors there were 12 treatment units which were repeated four (4) times so that there were 48 experimental units. The variables observed were variable of growth, production and characteristics of plants. The results showed that the among grasses species there were significantly different (P <0.05) on the variable of plant length, stem dry weight and leaf area, but did not different significantly (P> 0.05) on the variable number of leaves, number of tillers, leaf dry weight, root dry weight, total forage dry weight, leaf stem ratio with stem dry weight, and root toop ratio. The treatment of giving of levels biourine was significantly different (P <0.05) on all variables except stem dry weight, root dry weight, total dry weight, and toop root ratio. It can be concluded that Stenotaphrum secundatum grass responds to the highest growth and production compared to Axonopus compressus and Paspalum conjugatum . Biourine level 6000 l/ha (12 ml/4 kg) tend to be higher in providing growth and local grass production. There was no interaction between the types of local grass with various levels of biourine. Keywords: grass differences, biourine level, growth, production